Advanced Building Materials - Shukla S.K.; Kaul S. (My University, 2025)
The construction industry is going through a transformational period with the introduction of sophisticated building materials. This chapter examines recent advanced materials and breakthroughs in building materials to improve construction projects’ sustainability, performance, and efficiency. The development of ancient building materials is highlighted in the first part. It covers stone, clay, granite, lime, and basalt, including bamboo and wood as building materials. These materials are environmentally friendly, with lower carbon footprints. The developments in conventional building materials are covered in the second section. It covers the characteristics and uses of steel-reinforced concrete, synthetic fiber-reinforced concrete, and other reinforced concrete, steel, bricks, glass, and wood. The advances in building materials are covered in the last segment, like structural insulated panels, high-performance concrete, and self-healing concrete. These materials enable the creation of resilient structures that can survive dynamic loads and unfavorable climatic conditions thanks to their exceptional strength, durability, and design flexibility. The abstract also examines the idea of smart materials and how they can affect the construction sector. Smart materials have adaptable characteristics that react to environmental cues like temperature, light, or voltage. Shape memory alloys, phase-changing materials, and electrochromic glass are just a few of the qualities of these materials that make it possible to design comfortable and energy-efficient buildings. The chapter also highlights the importance of life cycle analyses and environmentally friendly building techniques in determining the total environmental impact of modern building materials. It emphasizes the necessity of continuing study and collaboration between experts in the field, academics, and policymakers to foster new developments and guarantee the practical application of these materials in construction projects. © 2025 selection and editorial matter, Shailendra Kumar Shukla; individual chapters, the contributors.